Numerical Simulation of Moving Load on Concrete Pavements - Lajčáková Gabriela (Transport and Telecommunication, 2015)
The knowledge of the development with time of the strain and stress states in pavement structures is needed in the solution of various engineering tasks as the design fatigue lifetime reliability maintenance and structure development. The space computing model of the truck TATRA 815 is introduced. The pavement computing model is created in the sense of Kirchhof theory of the thin slab on elastic foundation. The goal of the calculation is to obtain the vertical deflection in the middle of the slab and the time courses of vertical tire forces. The equations of motion are derived in the form of differential equations. The assumption about the shape of the slab deflection area is adopted. The equations of the motion are solved numerically in the environment of program system MATLAB. The dependences following the influence of various parameters (speed of vehicle motion, stiffness of subgrade, slab thickness, road profile) on the pavement vertical deflections and the vertical tire forces are introduced. The results obtained from the plate computing model are compared with the results obtained by the FEM analysis. The outputs of the numerical solution in the time domain can be transformed into a frequency domain and subsequently used to solve various engineering tasks.